2018
DOI: 10.2147/opth.s162233
|View full text |Cite
|
Sign up to set email alerts
|

Use of a novel extended blink test to evaluate the performance of two polyvinylpyrrolidone-containing, silicone hydrogel contact lenses

Abstract: BackgroundSustained digital display viewing reduces eye blink frequency and tear film stability. To retain water and preserve a smooth optical surface, contact lens manufacturers have integrated the humectant polyvinylpyrrolidone (PVP) into silicone hydrogel contact lenses. In this study, extended blink time (EBT) was used to assess visual stability over a prolonged blink interval of two PVP-containing silicone hydrogel lenses, samfilcon A (SAM) and senofilcon A (SEN).Materials and methodsThis randomized, bila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“… 39 Schafer et al reported that samfilcon A demonstrated a more wettable surface after blinking, compared to that of senofilcon A. 40 In our study, the value of the CA with samfilcon A was significantly lower than that of narafilcon A, indicating that samfilcon A had more wetting material than narafilcon A. This study is the first to evaluate the tear volume and prelens tear film stability in vivo, and the wettability of SCL materials in vitro.…”
Section: Discussionmentioning
confidence: 43%
“… 39 Schafer et al reported that samfilcon A demonstrated a more wettable surface after blinking, compared to that of senofilcon A. 40 In our study, the value of the CA with samfilcon A was significantly lower than that of narafilcon A, indicating that samfilcon A had more wetting material than narafilcon A. This study is the first to evaluate the tear volume and prelens tear film stability in vivo, and the wettability of SCL materials in vitro.…”
Section: Discussionmentioning
confidence: 43%
“…Since pVP can absorb water, it also plays the role of a countermeasure against diarrhea in medicine [ 56 ]. As pVP has the ability of easily forming a film, it is used in contact lenses [ 57 , 58 ]. It has also been used as blood plasma substitute, but finally was replaced by another substance [ 59 , 60 ].…”
Section: Popular Biomedical Applications Of Pvpmentioning
confidence: 99%
“…The two previous CLs patents have an improved gas permeability and are appropriate to the eye tissues. Recently, two CLs made of silicone hydrogel were integrated with Polyvinylpyrrolidone (PVP) to obtain a smooth water preserved CLs useful for people who are suffering from vision problems and working long time periods on computers (Schafer et al, 2018).…”
Section: Silicone Based Polymersmentioning
confidence: 99%